Making Sense of the Delivery of Non-Academic Student Support Services at Kyambogo University - Nakimul, Agnes (East African Journal of Education Studies, 2023)
The study explored how staff make sense of the delivery of non-academic student support services at Kyambogo University. Acquiring this deeper understanding was crucial because when staff make sense of their work, they are able to contribute to the fulfilment of the university’s objectives and are more driven to work for the good of others. When they see how their effort is having an impact and value on students, it also enables them to feel satisfied with their work. The study was based on semi-structured interviews with 11 staff who deliver non-academic student support services at Kyambogo University. The findings showed that staff made sense of their work when it benefited others than themselves. When the delivery of the services contributed to the creation of meaning, and when it resulted in their personal satisfaction, they were motivated to work more effectively and efficiently in order to support the success of all university stakeholders. The paper recommends that since the staff’s work aims to serve others’ needs and aspirations, management at Kyambogo University should provide assistance to staff in order to preserve the spirit of service by fostering a culture of trust and a safe psychological environment that motivates staff and secure their involvement, commitment, and dedication. Further, the delivery of the services leads to staff satisfaction when it satisfies the beneficiaries; hence, management should assist staff in achieving personal satisfaction since it motivates them to work by facilitating them in the form of workshops and conferences in order to build their capacity in the field